Weather stations and dendroclimatic studies in Mexico: Which station to choose? - Gutiérrez, Erick; Trejo, Irma; Bucio, Carolina; Luna, Jesús; Miguel, Alejandra; Ramírez, Minella; Vázquez, Mónica (Instituto de Ecología, A.C., 2022)
Tree-rings growth is a data bank that, if correctly interpreted in detail, can help elucidate climatic events of the past. To make more assertive interpretations it is necessary to use information from weather stations near the study sites. The objective of the present study was to determine if there are differences in conditions between the selected meteorological stations and the sampling sites used in the dendroclimatic studies carried out in Mexico. We reviewed different scientific databases and digital search engines to obtain all the published works related to dendroclimatology whose area of study is localized in Mexico. We obtained the values of each of the proposed variables, both the meteorological stations and the sampling sites used in the dendroclimatic studies to calculate an index of similarity of conditions proposed. We recorded 81 studies, but only 39 were analyzed (48%) since only they expressed in a precise way the stations used and the geographical coordinates of the sampling sites. We observed that only 6% of the dendroclimatic studies presented a high similarity, 41% of the studies showed a medium-high similarity, 46% showed a medium-low similarity, and the other 7% presented a low similarity of conditions. A comparison of conditions between meteorological stations and sampling sites should be made in all dendrochronological studies, which could be done with similarity indexes of conditions such as the one recommended in this study.